2019
DOI: 10.1007/978-3-030-35888-4_42
|View full text |Cite
|
Sign up to set email alerts
|

Train with Me: A Study Comparing a Socially Assistive Robot and a Virtual Agent for a Rehabilitation Task

Abstract: Long-term motor deficits affect approximately two thirds of stroke survivors, reducing their quality of life. An effective rehabilitation therapy requires intense and repetitive training, which is resource demanding. Virtual Agents (VAs) and Socially Assistive Robots (SARs) offer high intensity, repetitive and reproducible therapy and are thus both promising as rehabilitation tools. In this paper, we compare a SAR and a VA during a rehabilitation task in terms of users' engagement and movement performance, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Socially Assistive Robotics (SAR) is a domain of Human-Robot Interaction (HRI) which focuses on developing robots capable of assisting users through social interaction (Feil-Seifer and Matarić, 2005 ; Matarić and Scassellati, 2016 ). Unlike virtual agents, socially assistive robots present a physical embodiment, which improves likeability (Fasola and Matarić, 2013 ; Li, 2015 ), user engagement and motivation (Vasco et al, 2019 ), adherence (Bickmore and Picard, 2005 ; Kidd and Breazeal, 2007 ) and task performance (Vasco et al, 2019 ), which are essential in long-term healthcare programmes.…”
Section: Related Workmentioning
confidence: 99%
“…Socially Assistive Robotics (SAR) is a domain of Human-Robot Interaction (HRI) which focuses on developing robots capable of assisting users through social interaction (Feil-Seifer and Matarić, 2005 ; Matarić and Scassellati, 2016 ). Unlike virtual agents, socially assistive robots present a physical embodiment, which improves likeability (Fasola and Matarić, 2013 ; Li, 2015 ), user engagement and motivation (Vasco et al, 2019 ), adherence (Bickmore and Picard, 2005 ; Kidd and Breazeal, 2007 ) and task performance (Vasco et al, 2019 ), which are essential in long-term healthcare programmes.…”
Section: Related Workmentioning
confidence: 99%
“…Robot coaches have been used to encourage children exercising [10] and have been proved to be effective in terms of companionship and social interaction [10]. Previous research revealed that robot coaches are as effective as a human coach [11] and preferable to a virtual coach [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This tuned the ongoing development of robotic coaches towards the direction of humanoid robots or robots with some semblance of human-likeness [12]. Such developments involving humanoid robot coaches [12,13] engaged the users in upper limb training sessions. The robots (Bandit and R1) were larger in dimension, closer to human-size and mounted on a wheeled base.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies showed that embodiment plays a crucial role when investigating social cognition mechanisms (e.g. Vasco et al, 2019;Wiese, Metta, Wykowska, 2017), especially in the context of mutual gaze, with higher arousal and faster responses associated with real-time mutual gaze compared to direct gaze presented on a screen (Hietanen et al, 2008;Pönkänen et al, 2011).…”
Section: Resultsmentioning
confidence: 99%